As práticas corporais no cuidado em saúde mental em um CAPS II na Cidade de Serra/ES - Daltio, Gabriela Linhares (2018)
In Brazil, thinking about mental health care is experiencing issues that cross health and mental health policies in the workplace. Starting from the history of the struggle for Psychiatric Reform, substitution services to asylums, such as the Psychosocial Care Centers (CAPs), came on the scene to ensure that the treatment of people with mental disorders was permeated by several areas of knowledge. In order to broaden the discussion about the professional performance of Physical Education in Caps, I approach clues and problematizations of daily life. The objective of this dissertation is to analyze how corporal practices were organized and constituted in the care of users of Caps Mestre Álvaro of the Municipality of Serra / ES, based on the concepts of autonomy and empowerment present in Health Promotion and Mental Health Policies. The concept of autonomy aims at the potentialities and the development of the subjects' capacities for conscious choices about their actions and trajectories and that of empowerment presents itself as a process of stimulating subjects and collectives to acquire control of decisions and choices of adequate ways of life to their socio-economic-cultural conditions. For this research I used clues of the method of cartography to follow the routine of Caps and bring to the discussion events related to the daily life of Physical Education. To record this routine, I produce field diaries. When revisiting them I constructed two categories for analysis: "The Interaction with the community" and "Body Practices in the CAPS Mestre Álvaro?". The first one had as problematization the meetings that Physical Education provided with society and its reverberations (potentialities and tensions). In the second, the discussion about the role of the Physical Education teacher is able to go beyond the practice of movement itself, but also permeated by unpredictability. The concepts used were shown to be necessary, and their effectiveness in the world of work and in the living space / treatment of these individuals happened and can still happen amid tensions, disputes, contradictions.